In search of justice in Thailand's deep south Malay Muslim and Thai Buddhist women's narratives - Jamjuree, Soraya (Studies in religion and culture, 2022)
"This book gives a voice to the women, mostly Malay Muslim, of the Deep South of Thailand who, in the face of state intimidation or the violence of militant insurgency resulting from ethno-religious conflict, have drawn on their religious faiths to sustain the well-being of their families in the face of losing fathers, husbands, sons or brothers to the violence"--